(untitled) (Modern American Journal of Medical and Health Sciences, 2025)
Modern dental implantology actively integrates digital technologies to improve the precision and predictability of surgical interventions. The use of navigational surgical templates, created using cone-beam computed tomography data and digital jaw modeling, ensures prosthetic-oriented implant positioning with minimal deviations from the virtual plan (no more than 0.5 mm). This approach significantly reduces the risk of damage to anatomically significant structures, reduces surgical trauma, shortens its duration, and facilitates postoperative care. Computerized planning ensures uniform distribution of masticatory loads, highly aesthetic results, and the possibility of immediate or early orthopedic loading. Navigational implantation is particularly effective in complex clinical situations—multiple defects, complete edentulism, bone deficiency, and areas with high aesthetic demands. Thus, the use of computer technologies and navigation templates in dental implantology allows for the optimization of patient examination and treatment algorithms, increasing the safety and long-term effectiveness of rehabilitation.